Digital Evidence in Criminal Procedure: Legal Challenges and Solutions in Vietnam - Nguyen, Trương Thanh Thảo (Tạp Chí Khoa Học Và Công Nghệ Trường Đại Học Bình Dương, 2025)
The rise of digital technology poses challenges to Vietnam’s criminal justice system in applying digital evidence, despite its legal recognition in the 2015 Criminal Procedure Code. Significant gaps remain in evidence collection, preservation, and presentation, alongside inadequacies in cross-border data handling and privacy protection. This study suggests improving the legal framework through detailed regulations, advanced technologies like blockchain and AI, and enhanced judicial training to ensure the effective and lawful use of digital evidence, strengthening public trust in the digital age.